INVENTARISASI POLA AGROFORESTRI DI DESA TONSEA LAMA KECAMATAN TONDANO UTARA KABUPATEN MINAHASA - Mataputung, Sifan M.; Nurmawan, W.; Sumakud, Maria Y. M. A (Universitas Sam Ratulangi, 2019)
Agroforestry is a land management system used in combination with agricultural production that includes fruit trees and pastoral practices with forestry plants. One of the most efficient ways to solve pattern-related agroforestry problems is by using a central plant species that will play a role in multiple land uses. Inventory is the practice of listing plant and animal species in the forest, as well as potential resources. This study was done in Tonsea Lama village, North Tondano district, Minahasa regency, in the months of April to May 2018, with the purpose of making an inventory of agroforestry land use patterns. Result of this study are expected to provide actionable data for future studies on inventory of agroforestry patterns, as well as information for planning agroforestry patterns and land use. Data collection used purposive sampling methods. Agroforestry in Tonsea Lama village was found to follow the following patterns: 13 gardens with agrosilviculture patterns (86,67%) and 2 gardens with agrosilvopastoral patterns (13,33%). There were 74 different types of plants in the agroforestry systems.